Identification and morphological characterization of marine actinomycetes as biocontrol agents of Fusarium solani in tomato - Torres-Rodriguez, Juan; Reyes-Pérez, Juan; Castellanos, Thelma; Angulo, Carlos; Quiñones-Aguilar, Evangelina; Hernandez-Montiel, Luis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Fusarium spp. damages the roots of crops, its control is with synthetic fungicides, however, marine actinomycetes can be an option to the use of agrochemicals. The objective of this work was the identification and morphological characterization of marine actinomycetes as antagonists to Fusarium solani (Mart.) Sacc. Fusarium spp. was isolated from diseased tomato plants and mangrove sediment actinomycetes, both identified through taxonomic keys and molecular techniques. Eight isolates of Fusarium spp. were obtained, H8 being the most virulent and it was identified as F. solani. Thirty actinomycetes were isolated, of which only four inhibited the phytopathogen, being A19 the one that inhibited the fungus by 70% and was identified as Streptomyces sp. Marine actinomycetes may be an option for disease management in plants of agricultural interest.